Efeito de soluções contendo hexametafosfato de sódio e quercetina, associados ou não ao fluoreto, sobre o desgaste erosivo dentinário in vitro - Capalbo, Letícia Cabrera [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The aim of the present study was to investigate the effect of solutions containing fluoride (F), sodium hexametaphosphate (HMP) and quercetin (QC), alone or in association, on dentin erosion and on the inhibition of matrix metalloproteinases (MMPs) - 2 and -9, using in vitro protocols. Bovine root dentin blocks (4 × 4 × 2 mm; n = 96), selected by surface hardness, were randomly divided into 8 experimental groups (n = 12/group) and treated 2×/day (one minute) with the following solutions: (1) deionized water (negative control); (2) 1100 ppm F (“F”); (3) 1.0% HMP (“HMP”); (4) 0.03% QC (“QC”); (5) F+HMP; (6) F+QC; (7) HMP+QC; and (8) F+HMP+QC. Blocks were submitted to erosive challenges 4×/day for 5 days (dynamic exposure to 50 mmol.l-1 citric acid, pH 3.2, 90 s). They were then analyzed for dentin loss (profilometry) and integrated hardness loss in depth (area under the curve, ΔKHN). The antiproteolytic potential of solutions containing F, HMP and/or QC was analyzed by zymography. Dentin loss results (log10 transformed) were submitted to one-way ANOVA, followed by Tukey's test. ΔKHN data (raw) were submitted to two-way, repeated-measures ANOVA, followed by the Holm-Sidak test (p<0.05). The lowest dentin erosive wear was promoted by F+HMP+QC. At the lowest depths (5-30 μm), blocks treated with F+HMP+QC showed the highest values of ΔKHN. Zymography analysis showed that all treatments completely inhibited MMP-2 activity, except for QC administered alone (77% inhibition). For MMP-9, all the solutions containing HMP or the association of F+QC promoted total antiproteolytic activity. It was concluded that the addition of HMP and QC to F solutions led to greater protection against dentin erosion, both at the surface (dentin loss) and in relation to the mineral content of the remaining tissue (ΔKHN), in addition to promoting a complete inhibition of MMPs -2 and -9 activity in vitro.

O objetivo do presente estudo foi investigar o efeito de soluções contendo fluoreto (F), hexametafosfato de sódio (HMP) e quercetina (QC), sozinhos ou em associação, sobre a erosão dentinária e sobre a inibição de metaloproteinases da matriz (MMPs) -2 e -9, em protocolos in vitro. Blocos de dentina radicular bovina (4 × 4 × 2 mm; n = 96), selecionados por dureza superficial, foram aleatoriamente divididos em 8 grupos experimentais (n = 12/grupo) e tratados 2×/dia (um minuto) com as seguintes soluções: (1) água deionizada (controle negativo); (2) 1100 ppm F (“F”); (3) 1,0% HMP (“HMP”); (4) 0,03% QC (“QC”); (5) F+HMP; (6) F+QC; (7) HMP+QC; e (8) F+HMP+QC. Os blocos foram submetidos a desafios erosivos 4×/dia, por 5 dias (exposição dinâmica a ácido cítrico 50 mmol.l-1, pH 3,2, 90 s). Em seguida, foram analisados quanto à perda dentinária (perfilometria) e à perda de dureza integrada em profundidade (área sob a curva, ∆KHN). O potencial antiproteolítico das soluções contendo F, HMP e/ou QC foi analisado por zimografia. Os dados de perda dentinária (log10) foram submetidos a ANOVA um critério, seguido do teste de Tukey. Os resultados de ∆KHN (dados brutos) foram submetidos a ANOVA dois critérios, medidas repetidas, seguido do teste Holm-Sidak (p<0,05). O menor desgaste erosivo foi observado no grupo F+HMP+QC. Nas menores profundidades (5-30 µm), os blocos tratados com a solução contendo F+HMP+QC apresentaram os maiores valores de ∆KHN. A análise zimográfica mostrou que todos os tratamentos promoveram atividade antiproteolítica total da MMP-2, com exceção da QC administrada sozinha (inibição de 77%). Para MMP-9, todas as soluções contendo HMP e a associação de F+QC apresentaram atividade antiproteolítica total. Conclui-se que a adição de HMP e QC a soluções contendo F levou a uma maior proteção contra a erosão dentinária, tanto em superfície (perda dentinária) quanto em relação ao conteúdo mineral do tecido remanescente (∆KHN), além de promover uma completa inibição da atividade de MMPs -2 e -9 in vitro.
Effect of sodium hexametaphosphate and quercetin, associated or not with fluoride, on dentin erosion in vitro
Keywords: Erosão dentária; Fosfatos; Quercetina; Dentina; Inibidores de Metaloproteinases de Matriz; Tooth erosion